UTILIZATION OF HEALTH INFORMATICS IN CARDIOVASCULAR DISEASE - Dr.N.SASIKALA,; Dr.G.RASITHA BANU,; Dr.MURTAZA ALI, (International Journal of Pharma and Bio Sciences, 2016)
We are living in the modern world which had a great impact of technological development in various fields of the society. Within that there are several new advancements in medicines due to technology. This paper talks about the rapidity of health transition, across developing regions with consequent variations in the relative burdens of the dominant disease like CVDs. It discusses about the health informatics and its applications. The various reasons for CVD and its diagnosis patterns and new technologies.